2008
DOI: 10.1002/cncr.23536
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on upper extremity pain and dysfunction in head and neck cancer survivors

Abstract: BACKGROUND.Shoulder pain and disability are well recognized complications associated with surgery for head and neck cancer. This study was designed to examine the effects of progressive resistance exercise training (PRET) on upper extremity pain and dysfunction in postsurgical head and neck cancer survivors.METHODS.Fifty‐two head and neck cancer survivors were assigned randomly to PRET (n = 27) or a standardized therapeutic exercise protocol (TP) (n = 25) for 12 weeks. The primary endpoint was change in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
215
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 204 publications
(228 citation statements)
references
References 32 publications
11
215
2
Order By: Relevance
“…2,11 The results from our randomized controlled trial of upper extremity (UE) progressive resistance exercise training (PRET) demonstrated significant improvements in patient-rated shoulder pain and disability, UE strength and endurance, and range of motion in post-surgical HNC survivors. 12 All other outcomes, including fatigue, neck dissection impairment, and quality of life (QOL), favoured the PRET group at the end of the 12-week intervention but did not reach statistical significance. 12 In this article, we report the 12-month follow-up data from our randomized crossover trial comparing PRET with a standard therapeutic protocol (TP) in post-surgical HNC survivors.…”
Section: Ré Sumémentioning
confidence: 97%
See 2 more Smart Citations
“…2,11 The results from our randomized controlled trial of upper extremity (UE) progressive resistance exercise training (PRET) demonstrated significant improvements in patient-rated shoulder pain and disability, UE strength and endurance, and range of motion in post-surgical HNC survivors. 12 All other outcomes, including fatigue, neck dissection impairment, and quality of life (QOL), favoured the PRET group at the end of the 12-week intervention but did not reach statistical significance. 12 In this article, we report the 12-month follow-up data from our randomized crossover trial comparing PRET with a standard therapeutic protocol (TP) in post-surgical HNC survivors.…”
Section: Ré Sumémentioning
confidence: 97%
“…12 All other outcomes, including fatigue, neck dissection impairment, and quality of life (QOL), favoured the PRET group at the end of the 12-week intervention but did not reach statistical significance. 12 In this article, we report the 12-month follow-up data from our randomized crossover trial comparing PRET with a standard therapeutic protocol (TP) in post-surgical HNC survivors. Our study is one of the first to provide follow-up data on a resistance exercise intervention for shoulder pain and dysfunction after neck dissection in HNC survivors.…”
Section: Ré Sumémentioning
confidence: 97%
See 1 more Smart Citation
“…The PRET protocol, however, was tailored to each survivor based on baseline testing results and consisted of two sets of [10][11][12][13][14][15] repetitions, starting at 25-30% of their 1 repetition maximum (1-RM) strength, slowly progressing to 60-70% of their 1-RM by the end of the intervention period. Details of the PRET protocol have been published previously [5,12,13]. To summarize, participants in the TP arm of the trial performed a low-intensity resistance exercise program, while participants in the PRET arm performed a moderateintensity resistance exercise program.…”
Section: Exercise Training Interventionsmentioning
confidence: 99%
“…We previously reported that PRET was superior to TP for reducing shoulder pain and disability and improving upper extremity muscular strength and upper extremity muscular endurance [5]. The purpose of the present trial was to identify the key predictors of exercise adherence during the trial.…”
Section: Introductionmentioning
confidence: 99%